Anticorpos Anti-Toxoplasma gondii em pacientes renais, sob tratamento dialítico e transplantado, e sua associação com antígenos leucocitários humanos - Botelho, Marina Raduy (2012)
Toxoplasma gondii (T.gondii) is an obligate intracellular parasite of worldwide distribution infecting up to one third of the population and it has a great diversity of other species. There are several forms of presentation of this parasitosis, but most of the primary infections caused by T.gondii are asymptomatic due to immune system effectiveness. Immunocompromised individuals, such as patients on dialysis and the ones who received a transplant, have been a frequent target of opportunistic infections in which the clinical picture is considered severe with high morbidity and mortality indices. The infection is directly related to the immunity of the individual and the Major Histocompatibility Complex (MHC) is involved in this function. These molecules in human beings are called Human Leukocyte Antigens, or HLA system. The HLA genes are the most polymorphic of all mammal genes. The existence of hundreds of alleles in all loci allows the existence of a wide genotypic variability. This diversity as well as the polymorphisms of the HLA system genes together with the participation in the immune response, leads it to perform a major role in the pathogenesis of several diseases, however, little is known about the correlation between the HLA typing and toxoplasmosis in renal individuals. This study aimed to verify the prevalence of anti-T.gondii antibodies (IgM and / or IgG) and its correlation with the HLA class I (HLA-A and B) and class II specificities (HLA-DRB1) in patients on dialysis and who received a kidney transplant). This study population consisted of 203 patients on dialysis, 53 patients who receive a renal transplant and 73 healthy volunteers. For the detection and characterization of anti-T.gondii antibodies it was used the method ELISA, applying the quantitative Microparticle Enzyme Immunoassay (MEIA) (Abbott Diagnostics AxSYM® SYSTEM Toxo IgG and IgM antibodies to the T.gondii). For the HLA typing it was used the kit LABType® SSO One Lambda combined with the Luminex technology. Among the 256 patients on dialysis and who received a transplant, the seroprevalence of IgG antibodies was 133.11% and for IgM antibodies it was 0.99%.Among the 203 patients on dialysis, 68,96% were seropositive for IgG antibodies while among the 53 patients who received a transplant, 64,15% were positive for this antibody. Concerning the IgM antibody, only 0,99% of the patients undergoing treatment presented positivity, something which was not found in the patients who received a transplant. Analyzing the HLA typing and the association with the toxoplasmosis independently from the group of patients, we observed a higher frequency of the HLA class II specificities (DRB1*17 e DRB1*07) suggesting susceptibility to toxoplasmosi.